Corporate Social Responsibility: Strategic Implications* - McWilliams, Abagail; Siegel, Donald S.; Wright, Patrick M. (Journal of Management Studies, 2006)
abstract We describe a variety of perspectives on corporate social responsibility (CSR), which we use to develop a framework for consideration of the strategic implications of CSR. Based on this framework, we propose an agenda for additional theoretical and empirical research on CSR. We then review the papers in this special issue and relate them to the proposed agenda.